Contractual networks in European private international law - Grušic, Uglješa (Cambridge University Press, 2016)
This article examines private international law issues raised by transnational contractual networks. The focus is on choice-of-law questions that arise in the context of 1) relations between network members who are contractually bound to one another, 2) relations between network members not connected directly by bonds of contract, and 3) relations between the network and the outsiders. The aim is to assess whether, and to what extent, European private international law is capable of dealing with some of the key challenges posed by contemporary economic and social activity.